Heavy metal pollution and risk assessment of farmland soil around abandoned domestic waste dump in Kaifeng City - Wang, Lin; Zeraatpisheh, Mojtaba; Wei, Zhangdong; Xu, Ming (Frontiers in Environmental Science, 2022)
In order to understand the heavy metal pollution and potential ecological risk of farmland soil around the waste dump in the eastern suburb of Kaifeng clearly and provide a scientific basis for the remediation of heavy metals in farmland soil, the single factor pollution index method, Nemero comprehensive pollution index method and Hakanson potential ecological risk method were used to evaluate the heavy metal pollution status and potential ecological risk degree of farmland in this area at the same time. The ArcGIS software was employed to map the spatial distribution of heavy metal pollution and potential ecological risks. The results show that the average values of heavy metals in this area are higher than the soil Background Value of Kaifeng City, and the problem of excessive heavy metals in the soil is significant. Of the 40 surface soil samples, Cd's heavy and moderate pollution rates were up to 15% and 38%, respectively, and the potential ecological risk caused by Cd element was quite serious, and more than 35% of the soil samples were at higher potential ecological risk. The comprehensive review results showed that 38% of the samples were heavy pollution, and 23% of the sample soils were at higher potential ecological risk. The spatial distribution characterized by the levels of most heavy metals and the extent of potential ecological risk showed high levels in the center of the dumpsters, with a gradual decrease towards the outward radiation zone. This means dust and leachate from waste dumpsters are major causes of heavy metal contamination and potential ecological risks. In addition, the retrieval of the waste mound soil from landfills by villagers as soil fertilizer for rapeseed also caused, to some extent, the transfer of the waste mound contaminants.